Blood glucose related adverse drug reaction of antitumor monoclonal antibodies: a retrospective analysis using Vigibase - Yang, Jincheng (2023)
On the increasing prevalence of using mAbs (monoclonal antibodies) in cancer therapy and the severe risk of hyperglycemia, we aimed to analyze the main clinical ADRs of mAbs, with a focus on adverse hyperglycemic events associated with currently clinically used mAbs. mAbs as well as target information were selected from Martinadale book and published articles. Drug approving information was collected from each government website, and ADR statistic data were collected from VigibaseR, comparing with Adverse Event Reporting System of US FDA. Top 10 mAbs were classified within listing in total ADR records, ADRs per year, hyperglycemic ADR records. Vigibase data were updated onto 15 Feb 2019. 20 mAbs were analyzed with 263217 ADR reports, wherein 16751 records on Metabolism and nutrition disorders and 1444 records on Glucose metabolism disorders. The geographic, age, gender distributions and annual ADR report numbers were listed respectively. Of the top 10, Rituximab, Bevacizumab and Nivolumab were on the top 3 in total ADR record and hyperglycemic record. Top 3 record results were similar in Vigibase and FDA database. It is of increasing importance for clinicians to be aware of early detection, patient management, or drug selection strategies when using mAbs, particularly within the high glycemic risk-reported mAbs, to improve the efficacy and tolerability of mAbs regiment and optimize patient outcomes.